Furious depletion—Conceptualizing artisan mining and extractivism through gender, race, and environment - Côte, Muriel (Frontiers in Human Dynamics, 2023)
A buoyant debate has grown in political ecology and agrarian studies around the concept of extractivism. It shines a light on forms of human and non-human depletion that fuel contemporary capitalism. Within this debate however, artisan mining has been hard to fit in. Artisan mining is a form of small scale mineral extraction that occupies around 45 millions people around the world, and sustains the life of many more, especially in the Global South. Much research has looked at this expanding forms of livelihood, particularly through the prism o fits persistent informality, its labour organisation, and its challenges to environmental and labour rights. However it has not been well theorised in relations to extractivism, sitting uncomfortably with dominant categories such as ”the community”, ”the company” and ”social movements” in political ecology analyses. The paper maps out entry points to studying the significance of artisan mining within dynamics of extractive capitalism by bringing in conversation political ecology scholarship on extractivism and research on artisan mining through an ecofeminist lens. It develops the notion of “furious depletion”, attempting to capture the stark socioenvironmental injustice through which artisan mining forms an integral part of extractive capitalism, as both a victim and fuel thereof, while also emphasising the transformative political potentials of infuriation. It focuses specifically on the ways relations of gender and race mediate human-environment relations, can help clarify an understanding of artisan mining in the depletion dynamics underlying extractivism. Given the acceleration of mining as part of digital and energy transitions, and the expansion of artisan mining, an engaged conceptualization of artisan mining may support struggles away from extractive capitalism for the decades to come.